GOAL14 保護海洋生態 - 校務大數據研究中心; Center for Institutional Research and Data Analytics, NYCU (國立陽明交通大學校務大數據研究中心, 2022)
【學術研究】 海岸地形變遷AI偵測技術研發 發明水上垃圾智慧清運船，保護海洋生態 【社會公眾參與】 透過社團力量推動海洋保護觀念 【教育與育才】 南寮淨灘守護海洋 服務學習-淨灘及海廢監測 【校園運作】 限塑政策

【Research】 Research and Development of AI Coastline Topography Change Detection Technology Creating an Intelligent Aquatic Garbage Cleanup Vessel to Protect Marine Ecology 【Social Impact】 Promoting Marine Conservation Through the Power of Clubs 【Student Cultivation】 Protect the Ocean--Nanliao Beach Cleanup Service Learning--Beach Cleanup and Marine Waste Monitoring 【Stewardship】 Plastic Reduction Policies
GOAL14 Life Below Water